Ovaries are more vulnerable than hepatocytes for insulin resistance and hyperinsulinemia - Gültepe, İlhami and Başaranoğlu, Metin and Süleymanoğlu, Yaser and Başaranoğlu, Gökçen and Beyazıt, Fatma (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Non-alcoholic fatty liver disease (NAFLD) and polycystic ovary syndrome (PCOS) are common metabolic disorders. We aimed to evaluate the underlying mechanisms in the development of NAFLD and PCOS. Materials and Methods: Thirty female patients with NAFLD and without PCOS; 12 female patients with PCOS; and a control group with 17 healthy females were included. Pancreatic homeostatic model assessment-Beta cell function was measured by the homeostasis model assessment (HOMA)-B test. Results: The body mass index (BMI) of the NAFLD patients was higher than that of the PCOS patients (29.4±3.8 kg/m² vs 25.6±5.2 kg/m², p<0.05). There was no significant difference between the PCOS patients and controls with respect to BMI. The fasting insulin levels of the NAFLD patients were higher than those of the PCOS patients (5.06 unit more than PCOS, p<0.05) and 12.8 unit more than controls (p<0.001). The HOMA scores of the NAFLD patients were more than those of the PCOS patients (1.41 unit more than PCOS, p<0.05) and 2.95 unit more than controls (p<0.001). The HOMA-B score was higher in the NAFLD patients than in the PCOS patients. There was no statistical difference among the groups for serum triglyceride (p>.05) and cholesterol (p>.05). Conclusion: This study showed that rather than pancreatic beta-cell hyperfunction, insulin resistance plays a central role in the development of ovarian abnormalities.